PENERAPAN KEGIATAN EKSTRAKULIKULER PRAMUKA TERHADAP KETERAMPILAN SOSIAL SISWA KELAS 6 SD DR.SOETOMO V - Mochammad Rizal Alfaridho; Danang Prastyo; Via Yustitia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This thesis aims to analyze the influence of Scout extracurricular activities on thesocial skills of grade 6 students at SD Dr. Soetomo V. The method used in thisstudy is quantitative with data collection techniques through questionnaires. Theresults of the study show that Scout extracurricular activities have a positiveimpact on the development of students social skills, especially in the aspects ofcooperation, leadership, and interpersonal communication. The techniques usedare normality test, homogeneity test, and paired simple t-test hypothesis test.Based on the results of statistical tests carried out with t-tests, the significancevalue (Sig. 2-tailed) was 0.000 < 0.05. Based on the results of the conclusion inthe study carried out, it shows that there is a positive influence of scoutextracurricular activities on the social skills of elementary school students in gradeVI Dr. Soetomo V. It is hoped that students can apply these social skills instudents daily lives and schools can facilitate the existence of scoutextracurriculars